Geoelectric Investigation for Groundwater Prospects in Ejeme-Aniogor and Environs, Aniocha- South Local Government Area, Delta State, Nigeria - FI Chinyem (Journal of Applied Sciences and Environmental Management, 2017)
Geoelectric investigation for groundwater prospects in Ejeme-Aniogor and environs, Aniocha- South Local Government Area of Delta State, Nigeria was carried out with a view to determining the near subsurface lithologies and depths; as well as thickness of the various aquiferous zones/units in the study area. Fourteen vertical electrical soundings (VES) technique, employing the Schlumberger configuration were used in investigating the groundwater prospects, with maximum current electrode spacing of 500m. The acquired field data were interpreted quantitatively by partial curve matching and computer iteration. The result showed six to eight geoelectric layers with resistivities ranging from 120 to 1700 Ω for the topmost layer and 276 to 163000 Ω for the bottommost layer. The result also revealed that the depths to the various aquiferous zones ranged from 28.5 to 162 m while the thickness of the aquiferous zones ranged from 20.3 to 58.7 m. The aquiferous units in the study area were mostly confined and the results obtained from the study were found to be consistent with the lithologic logs obtained from borehole drilled in the study area. A generalized depth to the water table (acquiferous zones) cannot be deduced for the study area because it varied from one locality to another. However, the result showed that the area has good prospects for groundwater development.